Novel phenomenon of negative permittivity in silicon-based PiN diodes induced by electron irradiation. (January 2021) - Li, Yun; Gong, Min; Yang, Zhimei; Su, Ping; Ma, Yao; Fan, Sijie; Huang, Mingmin
Abstract: The negative permittivity of silicon-based PiN diodes is investigated experimentally in the frequency range from 1 Hz to 10 MHz, where electron irradiations and annealing thermal treatments are carried out. The permittivity is found be greatly affected by electron irradiations. In addition, the dispersion-free region is found be occurred in the samples irradiated by electron dose≥5.4646 × 10 14 e/cm 2 . Besides, annealing treatments also have an effect on the permittivity. It is interesting to find that, the annealing treatments lead to more negative platform (i.e., dispersion-free region) values of permittivity for samples irradiated by electron dose≥5.4646 × 10 14 e/cm 2, and the negative platform values under 350 °C annealing treatment are lower than that under 150 °C annealing treatment when the electron irradiation dose is higher than 1.0929 × 10 15 e/cm 2 . The novel phenomenon found in this work may provide new ideas for the application of semiconductor devices in information transmission, storage and processing. Highlights: The negative permittivity of silicon-based PiN diodes induced by electron irradiation is investigated experimentally. The negative permittivity in silicon-based PiN diodes can be induced by the electron irradiation. Annealing treatments can recovery recovery the permittivity in the case with a relatively low electron dose. The negative permittivity phenomenon in PiN diodes is considered be caused by defects induced by the electron irradiation.